PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP PEKERJA HARIAN LEPAS PADA CV. RATIH MANDIRI PERKASA CABANG UJUNGBATU - Fitria, Nova; Lestari, Rika; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Development is a matter that is indispensable for a country, especially fordeveloping countries. Development in the field of manpower and transmigration isessentially directed at the program and the empowerment of manpower andtransmigration competent, independent, high work ethic, welfare, and vibrantpartnerships as well as protection of rights as a whole. Implementation of the protectionof labor, the government has set regulations concerning employment,in Indonesia in theregulations of Law No. 13 Year 2003 on Employment (hereinafter referred Labor Law)and the Ministry of Manpower and Transmigration Republic of Indonesia Number:Kep.100 / Men / VI / 2004 provisions on Implementation of Work Agreement certain time(hereinafter Decree 100/2004).Based on the above background, the writer wanted knowing What rights andobligations of non-permanent employees at CV. Ratih Mandiri Perkasa BranchUjungbatu and What are the barriers faced by CV. Ratih Mandiri Perkasa UjungbatuBranch in the implementation of legal protection against non-permanent employees. Thistype of research is classified in socio legal research, research in this wear propertiesusing the description the method of research that seeks to describe and interpret theobject in accordance with what is, with the aim of describing systematically, facts andcharacteristics of the object under study as appropriate. This research was conducted inCV Ratih Mandiri Perkasa Ujungbatu, the data used is primary data, secondary data,and the data and the tertiary data collecting techniques results with interviews,questionnaires and a literature review.From the results, it can be concluded that, first the rights and obligations of nonpermanentemployees at CV. Ratih Mandiri Perkasa Branch Ujungbatu not performingwell, because the rights that should be accepted by the workers was not obtained aswages in accordance with the district minimum wage, lack of social security for nonpermanentemployees and the obligations should workers do also not implementedbecause many non-permanent employees come to work not on time. Second, barriersfaced by CV. Ratih Mandiri Perkasa Ujungbatu Branch in the implementation of legalprotection against non-permanent employees is lack of awareness CV. Ratih MandiriPerkasa legal protections of workers and the governments that Weak supervision of themanpower and transmigration and the absence of confirmation osanctions.Keywords: Legal protection, Casual workers off, rights and obligations